Figurative Language in Westlife Album “Coast to Coast” and My Chemical Romance Album "Welcome To Black Parade" - Gayatri Manuaba, I.A Intan; Tika, I Ketut (Humanis, 2019)
This study is entitled “Figurative Language in Westlife Album “Coast to Coast” and My Chemical Romance Album ‘Welcome to Black Parade”. The problems formulated in this study are the types of figurative language employed in Westlife’s and My Chemical Romance’s song lyrics and to find out how is the meaning of figurative language contrasted with its lexical meaning. There were five songs of Westlife chosen to be the source of first data, namely; Againts All Odds, I Lay My Love on You, My Love, What Makes a Man, and When You’re Looking Like That and five songs of My Chemical Romance also chosen to be the source of second data, namely; I Don’t Love You, The Sharpest Live, This How I Disappear, MAMA, and Welcome to Black Parade. The data were collected using documentation method then they were analyzed through qualitative method. After the data were analyzed and discussed, it was found that there were seven kinds of figure of speech employed in all the ten song lyrics; they were Simile, Personification, Hyperbole, Metonymy, Irony, Metaphor and Paradox. And then we find out the meaning of figurative language contrasted with its lexical meaning